ANALYZING THE QUALITY OF GROUND WATER IN KADUNA SOUTH LOCAL GOVERNMENT AREA, KADUNA STATE, NIGERIA - Yohanna, Paul; Apeh, Ocheme Victor; Lawuyi, Timothy (FUDMA JOURNAL OF SCIENCES, 2021)
The study examines the groundwater quality of Kaduna south Local government area. The physio-chemical analysis of PH, sulphate, Phosphate, chloride, Iron, Electrical conductivity, Turbidity, Nitrates, Total suspended solid and Total hardness were carried out, the result obtained were  compared with  World Health Organization (WHO) recommended standards for drinking water. pH, sulphate, electrical conductivity, chloride, nitrate, total suspended solids, and total hardness in all location were within the acceptable standards of WHO. The collected data from the laboratory analysis were analyzed using simple tables, graphs and charts and the result reveals that turbidity and iron in all location were above the acceptable standards of WHO. Turbidity which is above the WHO with a significant  value at all the eight sampling points with 25.3,22.6,28.7,11.6,9.05,9.05,10.4,14.3 NTU respectively, Iron  concentration in all the sampling points is high with 35.0, 30.0,26.0 15.0,12.0,10.0, 15.0,11.0 mg/l respectively. Large amounts of Iron in drinking water can give it an unpleasant metallic taste. Iron is an essential element in human nutrition, and the health effects of iron in drinking water may include warding off, fatigue and anaemia (metaglobinaemia).Groundwater exploitation especially boreholes should be regulated by government in order to reduce the negative effect of water pollution to humans. This research reveals there is great need to analyze any ground water before drinking
Keywords: Analysis, Quality, Ground, Water, Kaduna